The F# Language Design RFCs (F# 4.6) - Syme, Don; Carter, Phillip (Web, 2019)
The F# Language is a co-operation between the F# Community including contributors from Microsoft, Microsoft Research and GitHub. The RFCs for F# 4.6 have been developed by Don Syme, Phillip Carter and others and are available here: fslang-design/FSharp-4.6 at main · fsharp/fslang-design · GitHub